Exploring Conflict Management Strategies among School Administrators: A Case Study of an International Islamic School in Malaysia - Soubagleh, Moussa Khaireh (IIUM Journal of Educational Studies, 2020)
Abstract As educational organizations, schools are vulnerable to experiencing conflict. Notwithstanding the views of many scholars in the existence of functional conflict in a formal organization like school setting, proper management of conflict is required to be established by school administrators in order to ensure the smooth running of the school. The aim of this study was to explore the understanding of sources of conflict and conflict management among Islamic school administrators with the aim of formulating practical and effective strategies in conflict management within the school setting. The researchers used the qualitative case study method to explore the strategies adopted by three Islamic school administrators in handling conflict. The findings show that individual differences, commodification of education, school system and policy, human resource issues and practices, and attitude were the main factors giving rise to school conflict, while depression was identified as its resulting effect. The school needs to build trust, respect, stability, and teamwork into its atmosphere, culture and practices in order to prevent misunderstanding and conflict within its community. Keywords: Conflict management, functional conflict, dysfunctional conflict, Muslim administrators, Islamic schools, Islamic administration